The use of chitosan oligosaccharide to improve artemisinin yield in well-watered and drought-stressed plants - García-García, Ana L.; Matos, Ana Rita; Feijão, Eduardo; Cruz de Carvalho, Ricardo; Boto, Alicia; Marques da Silva, Jorge; Jiménez-Arias, David (Frontiers in Plant Science, 2023)
Artemisinin is a secondary metabolite well-known for its use in the treatment of malaria. It also displays other antimicrobial activities which further increase its interest. At present, Artemisia annua is the sole commercial source of the substance, and its production is limited, leading to a global deficit in supply. Furthermore, the cultivation of A. annua is being threatened by climate change. Specifically, drought stress is a major concern for plant development and productivity, but, on the other hand, moderate stress levels can elicit the production of secondary metabolites, with a putative synergistic interaction with elicitors such as chitosan oligosaccharides (COS). Therefore, the development of strategies to increase yield has prompted much interest. With this aim, the effects on artemisinin production under drought stress and treatment with COS, as well as physiological changes in A. annua plants are presented in this study. Plants were separated into two groups, well-watered (WW) and drought-stressed (DS) plants, and in each group, four concentrations of COS were applied (0, 50,100 and 200 mg·L-1). Afterwards, water stress was imposed by withholding irrigation for 9 days. Higher doses of COS caused an increase in leaf water potential and relative water content but no differences in dry weight and relative growth rate under DS were observed. COS treatment under DS also decreased antioxidant enzymes activities (especially APX and GR) as well as phenols and flavonoids content. Under drought stress the generation of H2O2 increased, while in WW plants a slight increase in dry weight and membrane fluidity (due to changes in fatty acid profile) was observed. Chitosan and its derivatives have potential to face the challenges of A. annua, but it is important to take in account its characteristics and the stress level applied to do not produce a detrimental effect on plant growth.